Recognition of Hijaiyah Letters with Punctuation Using Augmented Reality - Nisa'ul Hafidhoh; Tri Lestariningsih; Ardian Prima Atmaja; Muhammad Syaeful Fajar; Ikhwan Baidlowi Sumafta; Dinar Nur Izzah (Universitas Pendidikan Nasional, 2023)
Learning hijaiyah letters is an initial step to reading the Al-Qur'an. Because the Al-Qur'an is written in Arabic using hijaiyah letters with special punctuation. Currently, learning hijaiyah letters still uses simple media in the form of books, posters, display boards, etc. so it is less interesting. The rapid development of technology allows mobile devices to become smartphones that can be used as learning media. Therefore, mobile devices can be used for learning hijaiyah letters to make them more attractive. One technology that can be utilized is Augmented Reality which can combine the virtual world with the real world in the form of 3D through applications accessed on mobile devices. This research developed the introduction of hijaiyah letters equipped with punctuation and pronunciation using marker based augmented reality. The development of mobile application applies the Mobile Application Development Lifecycle (MADLC) method. The development of augmented reality applications utilizing Blender, Vuforia and Unity 3D Game Engine. The results of the Black box testing show that all functional requirements have been met and are running well.